INSIDENSI PENYAKIT VIRUS PADA TANAMAN CABAI (Capsicum anuum) DI DESA KAKASKASEN II KECAMATAN TOMOHON UTARA KOTA TOMOHON - Liho Adrian Vivaldy; Ratulangi Max M.; Manengkey Guntur S J. (COCOS, 2017)
ABSTRACTThe purpose and usefulness of this research is to know the incidence of viral disease in Chili (Capsicum anuum) in Kakaskasen Village II Tomohon Utara Subdistrict, Tomohon City and the benefit of research can provide information to related institutions especially for farmers about the existence of this virus disease in pepper plant to develop strategy Control of the disease. The research was conducted in Kakaskasen Village II, Tomohon Utara District, Tomohon City and the study lasted for four months. The results showed that the symptoms of viral pathogen attack on pepper plants occur in plants since 2 weeks transplanting and this happens until the generative phase plant because the disease is systemic. In morphology due to infection of plant virus into dwarf, change the color of leaves from green to a bit yellowish in addition to the slightly curly shape changes also curved upwards. The incidence of virus-causing pathogens in pepper plants in the first garden with an average percentage of 44.8%; Following the second plantation with an average percentage of 16.4%; And in the third garden with an average percentage of 22.67. Overall, the average incidence of virus-causing pathogen in Kakaskasen II village, Tomohon Utara sub-district, Tomohon city is 28%. Insect pests that attack the pepper plants Thrips sp, Bemisia sp and Myzus sp. The average population of insect pests as viral disease vectors are Thrips sp 89 individuals, Myzus sp 167 individuals, and Bemisia sp for 175 individuals. The more populations of vector insects the higher the incidence of disease.Keyword : Penyakit virus pada tanaman cabai